An acute case of Pimelea elongata toxicity in cattle in western New South Wales. Issue 1 (8th November 2022) - Cavanagh, C; Parry, S; Fraser, C; Dominiak, BC
Abstract : In May 2019, 96 cattle died from Pimelea toxicity in a period of 19 days after potential exposure, with the first deaths occurring within 5 days. After examining the circumstances, we suspect that several factors contributed to the deaths. These included that recently purchased stock and transported had access to flooded land containing Pimelea elongata. This weed species contains simplexin and 18 other compounds. Roots, flowers and seeds are significantly more toxic than the stem, branches and leaves. We suspect that thirsty and hungry stock consumed seed and roots from flooded pastures and consumed lethal doses of simplexin. Blood tests were not good indicators of the conditions. Management strategies are suggested.